Mirar desde adentro: producción audiovisual indígena frente a la violencia del archivo (REVISTA NODO, 2026)
This article analyzes a set of audiovisual practices by Indigenous women creators as critical interventions in hegemonic regimes of representation and in the ways archives have historically organized the image. By approaching the archive as a technology that fixes, classifies, and regulates meaning, the article proposes understanding audiovisual practices not merely as representational media, but as spaces for the production of situated memory, experience, and political agency.Drawing on the notion of looking from within, the text examines how these practices displace the position assigned to Indigenous images within institutional and media archives, activating forms of production that exceed their organizing logic. The analysis is based on a delimited corpus which allows for observing different regimes of visibility and their transformations. Rather than constituting a pure outside, these practices introduce fissures within regimes of registration and circulation, reconfiguring relationships between body, territory, time, and authorship from situated cultural frameworks. Engaging with visual culture studies and contemporary critiques of the archive, the article argues that these practices not only transform modes of representation, but also open zones of opacity where meaning does not fully stabilize, enabling alternative ways of thinking about images, memory, and knowledge beyond universal or hegemonic categories.